Modelling precipitation extremes in the Czech Republic: update of intensity–duration–frequency curves - Fusek, Michal; Hellebrand, Radek; Michálek, Jaroslav (Estonian journal of earth sciences, 2016)
Precipitation records from six stations of the Czech Hydrometeorological Institute were subject to statistical analysis with the objectives of updating the intensityâdurationâfrequency (IDF) curves, by applying extreme value distributions, and comparing the updated curves against those produced by an empirical procedure in 1958. Another objective was to investigate differences between both sets of curves, which could be explained by such factors as different measuring instruments, measuring stations altitudes and data analysis methods. It has been shown that the differences between the two sets of IDF curves are significantly influenced by the chosen method of data analysis.